Creating personalized partnerships across diverse districts - Freda Hicks; Megan Lyons (Emerald Publishing, 2024)
Purpose - This work aligns with two of the following NAPDS Essentials: Clinical Preparation and Learning and Leading. The authors collaborated with district partners to determine how to best meet their needs. Additionally, our institution continues to develop a reciprocal relationship; pre-service teachers can hone skills during the clinical field experience, and the university will better support the professional development initiatives of districts with whom we partner. Clinical field assignments are designed with intentionality to align with the needs of our districts. Consequently, pre-service teachers will be better equipped to immerse themselves in the field experiences and effectively address the diverse needs of students. The authors will continue to engage our preservice and in-service teachers and personalize supports. Design/methodology/approach - A needs assessment was conducted to determine the most appropriate supports for our district partners. A survey was disseminated, and individuals ranked their area for support. The authors followed up with in-service teachers and district leaders to discuss specific strategies that could strengthen academic achievement and social emotional development. Additionally, the data were used to determine how to better equip teacher candidates to serve in the partner districts. Findings - Two programs that have been highly successful have been the Teacher Assistant to Teaching Professional program which is a specialized grow your own and bringing high school students to campus that are interested in becoming educators their junior year, lastly, the use of Mixed Reality Simulations to strengthen educator preparation. Creating diverse partnerships is not a one-size-fits-all approach in every district. Needs assessment and ongoing conversations are needed to ensure both the district and the Educator Preparation Program are able to support pre-service and in-service teachers along with the needs of PreK-12 students. Originality/value - This paper highlights diverse approaches to strengthening partnerships and the teacher pipeline.